Influence of the addition of graphene nanoplatelets on the ballistic properties of HDPE/aramid multi-laminar composites. Issue 4 (4th March 2022) - de Tomasi Tessari, Bruna; Vargas, Natan; Rodrigues Dias, Rafael; Miranda Pereira, Iaci; Rossa Beltrami, Lilian Vanessa; Lavoratti, Alessandra; Poletto, Matheus; Zattera, Ademir José
ABSTRACT: The application of aramid fiber composites for ballistic purposes has increased in recent years. The addition of graphene in a polymeric matrix could boost the energy absorption and the ballistic protection of these composites. This study aims to investigate the performance of aramid fabric multi-laminar panels with high-density polyethylene (HDPE) films containing graphene nanoplatelets (GNP). Mechanical, dynamic-mechanical (DMA), ballistic impact, and split Hopkinson pressure testing were conducted. All composites obtained ballistic protection level III-A, with HDPE-0.5% GNP and HDPE-1% GNP obtaining the lowest subsequent deformations. HDPE-0.5% GNP showed the highest energy dissipation in DMA testing, corroborating the ballistic results. Graphical abstract: uf0001